Une archéologie des provinces septentrionales du royaume Kongo - Clist, Bernard,; Maret, Pierre de,; Bostoen, Koen A. G., (Archaeopress Publishing Ltd, 2018)
This text presents in detail the results of archaeological research carried out by the KongoKing project in the former northern provinces of the Kongo Kingdom, currently located in the Democratic Republic of Congo.